2014
DOI: 10.1002/eji.201444848
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor protein SAP regulates type II NKT‐cell development, cytokine production, and cytotoxicity against lymphoma

Abstract: CD1d-restricted NKT cells represent a unique lineage of immunoregulatory T cells that are divided into two groups, type I and type II, based on their TCR usage. Because there are no specific tools to identify type II NKT cells, little is known about their developmental requirements and functional regulation. In our previous study, we showed that signaling lymphocytic activation molecule-associated protein (SAP) is essential for the development of type II NKT cells. Here, using a type II NKT cell TCR transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The NKT cell transcription factor PLZF was found in all CD4 + cells and a significant proportion of DN T cells positive for NKG2D or NKG2A/C/E from Jα18 −/− MHCII −/− mice, consistent with the presence of NKT cells within these populations. The PLZF expression was very similar to what has been shown before for TCR‐transgenic 24αβ type II NKT cells ( and our unpublished data). The fact that all CD4 + T cells displaying NKG2A/C/E or ‐D expressed PLZF, although not all of these cells were CD1d‐dependent (as PLZF was seen in these populations also in CD1d −/− MHCII −/− mice), demonstrates that other non‐conventional T cells with similar phenotype are present in this population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The NKT cell transcription factor PLZF was found in all CD4 + cells and a significant proportion of DN T cells positive for NKG2D or NKG2A/C/E from Jα18 −/− MHCII −/− mice, consistent with the presence of NKT cells within these populations. The PLZF expression was very similar to what has been shown before for TCR‐transgenic 24αβ type II NKT cells ( and our unpublished data). The fact that all CD4 + T cells displaying NKG2A/C/E or ‐D expressed PLZF, although not all of these cells were CD1d‐dependent (as PLZF was seen in these populations also in CD1d −/− MHCII −/− mice), demonstrates that other non‐conventional T cells with similar phenotype are present in this population.…”
Section: Discussionsupporting
confidence: 89%
“…These TCR‐transgenic type II NKT cells (24αβ NKT cells) share several surface markers with type I NKT cells, such as NK1.1, CD122 and intermediate TCR levels, and are either CD4 + or CD4 − CD8 − . Further, type II NKT cells express the transcription factor PLZF, required for the development of type I NKT cells . Although transgenic 24αβ type II NKT cells share many features with type I NKT cells, 24αβ type II NKT cells exhibit other phenotypic traits (CD62L hi , CD69 neg/lo and CD49b + ), effector molecules (production of IFN‐γ rather than IL‐4), NK receptors, integrins and chemokine receptors distinct from type I NKT cells .…”
Section: Introductionmentioning
confidence: 99%
“…Using the approaches described above, many type II dNKT cells appear to share phenotypic and functional features with type I NKT cells such as high autoreactivity ( 62 ), PLZF- and SAP-dependent thymic development ( 54 , 63 ), constitutive expression of IL-4 mRNA ( 54 ), and the ability to secrete a wide range of cytokines rapidly after stimulation, including IFN-γ, IL-2, IL-4, IL-10, IL-17, GM-CSF, and cytolytic mediators such as perforin ( 54 , 63 ). Furthermore, many type II NKT cells have a CD44 high CD69 + CD122 + activated/memory phenotype, whereas CD62L is more or less expressed dependent on which transgenic mouse model is used, and can be divided into different subsets depending on CD4 and NK1.1 expressions ( 54 , 63 65 ). However, several studies suggest that type II NKT cells exist that are phenotypically and functionally distinct from type I NKT cells.…”
Section: The Cd1d-restricted T Cell Familymentioning
confidence: 99%
“…Moreover, their IL-13 production, in combination with TNF-α, led to up-regulation of TGF-β secretion by myeloid-derived suppressor cells (MDSC), and resulted in decreased cytotoxic T cell activity ( 161 ). Interestingly, in contrast to their notable immunoregulatory role in anti-tumor responses, two recent studies have highlighted the ability of type II NKT cells to contribute to anti-tumor immunity in response to CpG in a B16 melanoma model ( 54 ), and by their ability to directly kill lymphoma cells in vitro ( 63 ). Thus, type II NKT cells can suppress anti-tumor immunity, counteracting the anti-tumor activity of type I NKT cells, but can also contribute to defense against tumor growth.…”
Section: Functions Of Type II Nkt Cellsmentioning
confidence: 99%
“…Studies of type II NKT cells are limited by a lack of specific markers for these cells and by a paucity of techniques that permit their analysis (by contrast, i NKT cells can be readily and specifically detected using CD1d/α-GalCer tetramers) ( 73 ). However, several experimental strategies have enabled study of the functions of type II NKT cells; these include the use of Jα18-deficient IL-4 reporter mice ( 74 ) and 24αβ transgenic mice that express the TCR of a type II NKT cell clone ( 75 ). These studies showed that, like i NKT cells, type II NKT cells develop via a linear maturation process marked by changes in expression of CD44 and NK1.1; moreover, like i NKT cells, they differentiate into NKT1, NKT2, and NKT17 cells, as shown by their expression of key transcription factors.…”
Section: The Cd1 Family Of Lipid Antigen-presenting Moleculesmentioning
confidence: 99%